SUPPLY CHAIN MANAGEMENT OF TOMATO PRODUCTION AT MADANAPALLE REGION: A CASE STUDY - M V Durga Prasad (UPT Penerbitan Universitas Jember, 2012)
Active players/Stakeholders in the entire supply chain of tomato production at Madanapalle region starting from the seed manufacturer to the buyers in the market were identified. A survey was conducted in 34 sampled villages with 690 small/medium business farmers who were interviewed to know the cost of tomato production and also to know about the satisfaction levels of the services provided by various stakeholders in the supply chain. Interviews with all the remaining players/stakeholders in the supply chain were conducted through an unstructured questionnaire. During this study each player’s revenue and risks were noted and observed that farmer and urban end user got most affected due to market pricing. A new pricing model is proposed and will help in developing a rural-urban linkage.